1D Audio Magnetotelluric Modelling for Deep Aquifer Identification in the Lava Fan Area of Haruman Peak, Malabar Mountains - Rahmawati, Nabilah; Kusuma, Nabila Putri; Hanifah, Shofie Dzakia; Junursyah, G.M. Lucki; Harja, Asep (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
The Malabar Mountains area acts as a catchment and infiltration zone for rainwater. Haruman Peak is the location of one of these areas. Information on the well-preserved depth of the shallow aquifer at 40 meters reinforces this. This research reviews the results of subsurface 1D resistivity structures from AMT data to obtain information on the depth of deep aquifers on the western slope of the Haruman Peak Lava Fan, Haruman Mountains. 1D modelling shows an aquifer at depth of 140.56-2080.07 meters with resistivity ranging from 5.25-68.08 Ωm. At depths of 453.32 m (HR02), 530.8 m (HR03), 1464.97 m (HR01), and 2080.07 m (HR02), interbedded tuff-andesite with minor pumice identifies the deep aquifer. In addition, a depth of 140.56 m (HR02) with a resistivity value of 68.08 Ωm indicates a shallow aquifer. Looking at the elevation of the Bandung Basin, water from aquifers located at elevations > 700 meters above sea level will flow into the Bandung Basin.